Drop Foot After Spinal Anesthesia - Dhanu Enggar; Surachtono (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2023)
Neurological complications after spinal anesthesia are very rare and often transient. The prevalence has been reported as 0–36 per 10 000 cases after epidural anesthesia and 35 per 10 000 cases after spinal anesthesia. A healthy 25 years old man was arranged for elective ESWL therapy due to a stone in the right upper ureter. The patient was categorized ASA I, spinal anesthesia was performed using a 27 gauge pencil-point spinal needle into L3-L4 space in a sitting position. During the procedure of inserting spinal needle the patient had no complaints. After the withdrawal of the cerebrospinal fluid, 4 ml of hyperbaric bupivacaine 0.5% was injected and the patient was moved to a supine position. The operative procedure went well without any complications. Six hours after surgery patient was unable to move his left foot meanwhile the right foot was normal. The neurologist was consulted and the patient was treated using methylprednisolone iv, mecobalamin, and pregabalin. MRI of the lumbosacral showed normal results, EMG studies showed a functional partial lesion on the left radix of L4-5, L5-S1. After 7 days of treatment, the patient felt improvement in his symptoms, and the patient was discharged. Patient came for a follow-up to neurologist & physiotherapist until 24 days after surgery, and the symptoms were gradually get resolved. Management of neurological complications after spinal anesthesia depends on its etiology, so it’s important to do an early diagnosis to make a further treatment.